Digitising Indigenous Heritage: A Bibliometric Study of Equity, Access, and Representation in Global Research - Mondal, Debdas (Information Research Communications, 2026)
The digitisation of indigenous heritage has emerged as a vital field bridging technology, culture, and social justice. This study presents a comprehensive bibliometric analysis of global research on digitising indigenous heritage, with a specific focus on equity, access, and representation. Using data extracted from the Scopus database (2000–2025), a total of 628 publications were analysed to identify growth trends, document types, leading countries, key authors, and thematic clusters. The findings reveal a steady and significant growth in research, particularly after 2015, reflecting the increasing recognition of digital heritage as a tool for cultural preservation and empowerment. Australia, Canada, and the USA emerged as the most active contributors, while journals such as Digital Heritage International Journal and Journal of Cultural Heritage led in publication output. Keyword co-occurrence analysis identified four dominant research clusters: Cultural Preservation, Equity and Access, Indigenous Representation, and Ethical Frameworks, indicating a multidimensional evolution from technology-driven initiatives to community-centred and ethically guided approaches. Despite notable progress, challenges persist regarding ownership, consent, and the equitable participation of indigenous communities in digitalisation processes. The study concludes that fostering inclusive, culturally sensitive, and ethically informed digital heritage practices is essential for achieving true equity and sustainability in preserving indigenous knowledge.
Keywords: Access; Bibliometric analysis; Digital humanities; Digitisation; Equity; Indigenous heritage; Representation.